Crystal structures and the electronic properties of silicon-rich silicon carbide materials by first principle calculations. Issue 11 (November 2019) - Alkhaldi, Noura D.; Barman, Sajib K.; Huda, Muhammad N.
Abstract: Silicon carbide has been used in a variety of applications including solar cells due to its high stability. The high bandgap of pristine SiC, necessitates nonstoichiometric silicon carbide materials to be considered to tune the band gap for efficient solar light absorptions. In this regards, thermodynamically stable Si-rich Six C1-x materials can be used in solar cell applications without requiring the expensive pure grade silicon or pure grade silicon carbide. In this work, we have used density functional theory (DFT) to examine the stability of various polymorphs of silicon carbide such as 2H–SiC, 4H–SiC, 6H–SiC, 8H–SiC, 10H–SiC, wurtzite, naquite, and diamond structures to produce stable structures of Si-rich Six C1-x . We have systematically replaced the carbon atoms by silicon to lower the band gap and found that the configurations of these excess silicon atoms play a significant role in the stability of Si-rich Six C1-x . Hence, we have investigated different configurations of silicon and carbon atoms in these silicon carbide structures to obtain suitable Six C1-x materials with tailored band gaps. The results indicate that 6H-Six C1-x is thermodynamically the most favorable structure within the scope of this study. In addition, Si substitution for C sites in 6H–SiC enhances the solar absorption, as well as shifts the absorption spectra toward the lower photon energy region. In addition, in the visible range the absorption coefficients are much higher than the pristine SiC. Abstract : Condensed matter physics; Materials chemistry; Materials science; Si-rich-silicon carbide; Photovoltaic; Density functional theory